Mathematical Modeling and Kinematic analysis of 3-RRR Planar Parallel Manipulator - Himam Saheb, Shaik; Satish Babu, G. (EAI Endorsed Transactions on Energy Web, 2021)
Parallel mechanisms are found as positioning platforms in several robot manipulator applications tool manufacturing applications. Today, various types of these mechanisms are classified based on the structure, type of joints, and degree of freedom. An important and basic planar mechanism providing three degrees of freedom at the end-effector (movable platform) is a 3-RRR linkage. The forward kinematics in parallel mechanisms is a multi-solution problem and involves cumbersome calculations compared to inverse kinematics. With forward kinematics, the input kinematic parameters for any manipulator are known, and the end effector coordinate must be determined. The kinematic equations are generated with mechanics principles, and Jacobian matrices are formulated, With the Jacobian matrix, the regular workspace and dexterous workspace analysis calculated. The main objective is to fabricate a model of this planar manipulation mechanism with calculated dimensions and observe the practical workspace and dexterous workspace available at the end effector. The practical workspace and calculated workspace is presented in this paper. This final output data is useful for manipulator designers to design manipulators for different applications. In addition to this, the stress analysis is performed with Ansys software’s help to estimate the moving platform’s failure zone.
Keywords: 3RRR Parallel Planar Manipulator; Workspace analysis; Regular Dexterous Workspace; fabrication of 3RRR PPM Model; Performance analysis; Stress analysis; load-carrying capacity; precise and accurate position